Deploying solar pumps at scale in South Asia: opportunities for solarizing agriculture in South Asia - Verma, Shilp; Patel, Kalpana; Neupane, Nilhari; Shrestha, Shisher (International Solar Alliance, 2025)
South Asia is home to the world’s largest pumped irrigation economy, with more than 30 million energized minor irrigation structures supporting over 100 million hectares of cropped area. Driven largely by private investments from millions of small and poor farmers, this infrastructure underpins regional food security for 1.6 billion people, yet it also contributes to severe groundwater depletion, rising greenhouse gas emissions, and chronic financial distress among electricity utilities. Across Bangladesh, Bhutan, India, Maldives, Nepal, and Sri Lanka, rising energy demand, expanding rural electrification, and abundant solar resources create a strong case for accelerating the transition to solar-powered irrigation. With an estimated potential of more than 25 million deployable solar pumps and a market potential exceeding USD 120 billion, solarization is poised to reshape South Asia’s water-energy-food systems. This report synthesizes field experience, policy experimentation, and analytical work on solar irrigation technologies to outline a practical roadmap for the region’s transition. Key recommendations include creating enabling policy environments, designing context-appropriate business and deployment models, reducing system costs, innovating financial instruments, promoting optimal pump utilization, and strengthening capacity and awareness. The report also highlights priority actions for ADB and ISA, including detailed country assessments, establishment of a solar pump innovation fund, regional scaling of sizing tools, and development of platforms for south–south learning and cooperation.